A COARSE-GRAINED MODEL OF DNA WITH EXPLICIT SOLVATION BY WATER AND IONS - DeMille, Robert C. (2010)
Solvation by water and ions has been shown to be vitally important for biological molecules, yet fully atomistic simulations of large biomolecules remain a challenge due to their high computational cost. The effect of solvation is the most pronounced in polyelectrolytes, of which DNA is a paradigmatic example. Coarse-grained (CG) representations have been developed to model the essential physics of the DNA molecule, yet, almost without exception, these models replace the water and ions by implicit solvation in order to significantly reduce the computational expense. This work introduces the first coarse-grained model of DNA solvated explicitly with water and ions. To this end, we combined two established CG models; the recently developed mW-Ion model [DeMille, R. C. and Molinero, V. J. Chem. Phys. 2009, 131, 034107], which reproduces the structure of aqueous ionic solutions without electrostatic interactions, was coupled to the 3-Sites-Per-Nucleotide (3SPN) CG model of DNA [Knotts, T. A. IV; et al. J. Chem. Phys. 2007, 126, 084901]. Using atomistic simulations of d(CGCGAATTCGCG)(2) as a reference, we optimized the coarse-grained interactions between DNA and solvent to reproduce the solvation structure of water and ions around CG DNA. The resulting coarse-grained model of DNA explicitly solvated by ions and water (mW/3SPN-DNA) exhibits base-pair specificity and ion-condensation effects and it is two orders of magnitude computationally more efficient than atomistic models. We describe the parameterization strategy and offer insight into how other CG models may be combined with a coarse-grained solvent model such as mW-Ion.